The GeoRSS Model and the Design of a Ranking Algorithm in Semantic Web - Bennani, Anas; Khoulji, Samira; Larbi, Kerkeb Mohamed (Transactions on Engineering and Computing Sciences, 2017)
E-commerce has become nowadays an influential actor in the international trade industry and has greatly contributed in the economic development of nations. The fact of dealing with this field along with the evolution of technologies renders the e-commerce more usable by internet users. The semantic web offers advanced technical solutions relying on the structuring and organization of the existing data on the web. Throughout this Paper, I will tackle the issue of e-commerce in relation to geolocation, while at the same time offering the internet user more freedom to detect the surface of the geographical area where he/she is located by a proposing a new geographical coordinate classification algorithm.